2017
DOI: 10.1021/acs.jced.7b00886
|View full text |Cite
|
Sign up to set email alerts
|

Cross Second Virial Coefficients and Dilute Gas Transport Properties of the (CH4+ C3H8) and (CO2+ C3H8) Systems from Accurate Intermolecular Potential Energy Surfaces

Abstract: Accurate values for the cross second virial coefficients and dilute gas shear viscosities, thermal conductivities, and binary diffusion coefficients of the (CH 4 + C 3 H 8 ) and (CO 2 + C 3 H 8 ) systems were determined at temperatures from (150 to 1200) K using state-of-the-art computational approaches. The cross second virial coefficients were calculated semiclassically using the Mayer-sampling Monte Carlo method, while the transport properties were computed by means of the classical trajectory approach in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 67 publications
(235 reference statements)
5
25
0
Order By: Relevance
“…The high-temperature data (T > 298 K) of Kestin and Ro are known to suffer from a design flaw 71 in their viscometer that resulted in viscosity values that are always systematically too high above room temperature by up to about 1%. 5,10,13,14,16,17,65 This is consistent with the observed deviations. We conservatively estimate the combined standard uncertainty of the scaled values to vary from 0.2% for pure CO 2 to 0.15% for pure N 2 between 300 K and 700 K, increasing to 1% for pure CO 2 and 0.5% for pure N 2 , respectively, outside of this temperature range.…”
Section: B Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The high-temperature data (T > 298 K) of Kestin and Ro are known to suffer from a design flaw 71 in their viscometer that resulted in viscosity values that are always systematically too high above room temperature by up to about 1%. 5,10,13,14,16,17,65 This is consistent with the observed deviations. We conservatively estimate the combined standard uncertainty of the scaled values to vary from 0.2% for pure CO 2 to 0.15% for pure N 2 between 300 K and 700 K, increasing to 1% for pure CO 2 and 0.5% for pure N 2 , respectively, outside of this temperature range.…”
Section: B Results and Discussionsupporting
confidence: 91%
“…Binary diffusion coefficients measured by the Dunlop group are consistently in excellent agreement with theoretically calculated values as illustrated for other dilute gas systems. 17,93 The other experimental data shown in Fig. 7 exhibit larger scatter and have larger uncertainties than that of Robjohns and Dun-lop, especially the high-temperature data of Pakurar and Ferron, which have quoted uncertainties of 10%.…”
Section: B Results and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In our previous studies of intermolecular PESs involving hydrocarbons, ,,,, we observed systematic positive deviations of the ab initio calculated values for the second virial and cross second virial coefficients from most of the experimental data. This is mainly due to the use of rigid monomers, resulting in the neglect of important vibrational contributions to the dispersion coefficients, see ref and references therein.…”
Section: Intermolecular Potential Energy Surfacementioning
confidence: 69%